The Role of Work-Based Learning in Enhancing Career Adaptability: An Empirical Study from Vocational Students in Indonesian and Malaysian Universities - Tuatul Mahfud; Alias Masek; Suyitno Suyitno; Ade Novi Nurul Ihsan; Yulia Fransisca; Ponco Wali Pranoto; Aji Pranoto; Samsul Hadi; Arif Susanto (National Research Mordova State University, 2024)
Introduction. Career adaptability has been recognized as one of the skills needed to face changing needs in the world of work. This study is increasingly interesting from the perspective of instilling career adaptability in a vocational university environment. The importance of mastering career adaptability has been established, but the interaction between predictors such as work-based learning factors, curriculum relevance, university support, career self-efficacy has not been well-defined. This study aims to investigate the role of work-based learning, curriculum relevance, university support, and career self-efficacy on university students' career adaptability. Materials and Methods. We involved 476 vocational students from universities in Indonesia and Malaysia. The data analysis used structural equation modelling (SEM) to test direct and indirect effects of career adaptability. The study utilizes the Amos 18 software for SEM analysis. This study used 200 bootstrap samples and a bias-corrected confidence interval of 90% to analyse the mediation role. Results. The study results reveal that work-based learning, curriculum relevance, university support, and career self-efficacy directly influence the career adaptability of vocational students. Another finding is that career self-efficacy was proven to mediate the effect of work-based learning and university support on vocational students' career adaptability. Career self-efficacy does not mediate the effect of curriculum relevance on vocational students' career adaptability. Discussion and Conclusion. The results of this study provide important implications for vocational education practitioners to promote career adaptability in the university environment through various work-based learning programs, curriculum relevance, university support, and career self-efficacy. Also, the result will guide the ongoing WBL curriculum review and improvement in Malaysia and Indonesia.